Penyuluhan dan Pendampingan Produk Halal pada Kelompok Usaha Makanan Gogos - Addury, Multazam Mansyur; GH, Nur Hishaly; Herawati, Hasmiah; Hidayat, Ardi; Ridwan, Muhammad (Abdimas Indonesian Journal, 2024)
This research aims to help Gogos food businesses in the process of obtaining halal certification through Community Service activities. The Community Service was conducted with a participatory approach, involving the food businesses as active partners throughout the process. The first step was to coordinate and discuss the issues and the urgency of halal certification. Then, a problem-solving discussion was conducted to find joint solutions to overcome the obstacles faced by the food businesses. During the education sessions, the food businesses were provided with information about the importance of halal certification, the steps for obtaining it, and the requirements to be fulfilled. The Community Service team also assisted the businesses in the registration process and the implementation of the Halal Product Process (PPH) by the Halal Product Assurance Agency (BPJPH). The evaluation results showed an increase in awareness and knowledge among the food business owners regarding the urgency of halal certification.